2016
DOI: 10.1039/c6dt00245e
|View full text |Cite
|
Sign up to set email alerts
|

Studies of viomycin, an anti-tuberculosis antibiotic: copper(ii) coordination, DNA degradation and the impact on delta ribozyme cleavage activity

Abstract: Viomycin is a basic peptide antibiotic, which is among the most effective agents against multidrug-resistant tuberculosis. In this paper we provide the characteristics of its acid base properties, coordination preferences towards the Cu(ii) ions, as well as the reactivity of the resulting complexes against plasmid DNA and HDV ribozyme. Careful coordination studies throughout the wide pH range allow for the characterisation of all the Cu(ii)-viomycin complex species. The assignment of proton chemical shifts was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…Furthermore, these elements are considered as possible key aspects in various contagious infections. Various facts stated that a few transition elements facilitate immune system inhibit microorganisms such as Mycobacterium TB [25,26]. The ingestion of toxic elements may lead to pulmonary TB, myocardial infarctions and atherosclerosis related disorders by rising oxidative stress caused by deficiency of an antioxidant element Zinc [27].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, these elements are considered as possible key aspects in various contagious infections. Various facts stated that a few transition elements facilitate immune system inhibit microorganisms such as Mycobacterium TB [25,26]. The ingestion of toxic elements may lead to pulmonary TB, myocardial infarctions and atherosclerosis related disorders by rising oxidative stress caused by deficiency of an antioxidant element Zinc [27].…”
Section: Introductionmentioning
confidence: 99%
“…A set of evidences indicated that some transition metals help immune system suppress microorganisms such as Mycobacterium tuberculosis. [10], [11]…”
Section: Introductionmentioning
confidence: 99%
“…It is currently mainly used for the treatment of tuberculosis, and its anti-tumor effect has not been previously mentioned in relevant studies. 34,35 We speculate that viomycin may be used for the targeted treatment of patients with metastatic OS. Taken together, we identified a series of drugs that interact with MRSs through reverse screening, providing more potential options for the treatment of patients with metastatic OS.…”
Section: Discussionmentioning
confidence: 99%